(untitled) (CIPEEX, 2025)
Animal experimentation is a practice potentially used in science and in the development of medicines and cosmetics. However, the decision to use animals is usually driven by the lack of viable alternatives to achieve the objectives of the research, which raises complex ethical issues and demands other accessible methods . Advances such as cell cultures, co-cultures, and three-dimensional (3D) cultures, known as organoids, allow the reproduction of human tissue functions and structures, reducing the use of animal testing and promoting more ethical practices in science. The present study aimed to analyze new technologies that replace or decline the use of animals in scientific research, highlighting the importance of cell models and their ethical and technological impact. This is a descriptive literature review, conducted based on the Pubmed and ScienceDirect databases, prioritizing recent publications (2021–2024). After analyzing the articles, it was possible to identify the evolution of in vitro methods, starting with the biocompatibility test, in which a mammalian cell monolayer was covered with agar to evaluate plastics used in medical and hospital articles and identify toxic effects on cells. From this, cell cultures emerged, such as monocultures (a single cell type) and co-cultures (interaction between different cell types). More recently, 3D cultures or organoids have been developed, structures derived from stem cells that reproduce morphological, functional, and molecular aspects of real organs. With these advances, more accurate approaches have emerged, such as organ-on-a-chip, microfluidic devices that simulate the biochemical and mechanical environment of human tissues. These models are encouraged by Law 15.183/25, which prohibits cosmetic testing on animals in Brazil, promoting an important advance for predictive science, enabling safety and efficacy at lower cost, with greater agility and, above all, without the use of animals, contributing significantly to the consolidation of more ethical practices in scientific research. Cell models offer effective and ethical solutions to replace animal experimentation, meeting the concept of the 3 Rs, characterized as reduction, refinement, and replacement, which in summary means reducing the number of animals used in research, improving the conduct of studies in order to reduce suffering to a minimum, and seeking methods to replace in vivo testing. It is concluded that well-designed cellular models can offer essential knowledge for areas of study that promote the health and well-being of society, completely replacing animal experimentation without compromising scientific quality, contributing to the consolidation of the 3Rs culture in practice.